WildCare: a mobile application for accessible wildlife rehabilitation and public education - Troyan, Hayley, author; Dewey, Tanya, advisor; Ruzicka, Becky, advisor (Colorado State University. Libraries, 2025)
Wildlife rehabilitation is an important interface between conservation science and public engagement, yet members of the public often lack accessible, accurate guidance when encountering injured or orphaned animals. Each year, rehabilitation centers across North America admit thousands of animals, with the majority of cases linked to human activity such as vehicle collisions, domestic pet attacks, and unnecessary intervention driven by misinformation. Although websites, pamphlets, and hotlines are widely available, these resources are often fragmented, difficult to access in urgent situations, and limited in scope (Cox, 2021; Miller et al., 2023). This thesis project proposes the development of WildCare, a mobile application designed to increase accessibility, reduce misinformation, and connect the public directly to wildlife rehabilitation centers. The app integrates features such as species identification guides, an emergency decision tree, and location-based center directories, while also providing educational resources on ethical and ecological considerations. By synthesizing scientific literature, professional ethical standards, and models from successful conservation apps, this project frames the app as both a technological innovation and a conservation tool. The expected benefits include reduced harm to wildlife, streamlined intake processes for rehabilitation centers, and improved public understanding of ecological systems. Ultimately, WildCare demonstrates how mobile-first design can strengthen community engagement and support wildlife conservation outcomes.
Keywords: wildlife; app; rehabilitation; public